Deriving Spatial Metropolitan Wide Patterns of Quality of Life Dimensions From Survey Data: the Case of the Brisbane-South East Queensland Region in Australia - Robert Stimson; Prem Chhetri; John Western (European Regional Science Association (ERSA), 2006)
Quality of life studies typically focus either on aggregate measures of QOL variables using secondary data sources for aggregated spatial units or on primary data collected through sample surveys whereby individuals provide subjective assessments of QOL dimensions. This paper uses sample survey data collected in a 2003 survey of QOL using a spatially stratified sample design across the Brisbane-South East Queensland (SEQ) region, Australia's fastest growing metropolitan region in the 'sun belt'. Multi-variate statistical modelling and GIS-based spatial modelling techniques are used to derive summary masures of QOL dimensions from the survey data and to then produce estimated spatial patterns of QOL dimensions across the residential neighbourhoods comprising the SEQ region.
Keywords: 330